Analysis of Students' Perception on MBS Program in Chitwan - Pokhrel, Jagannath (Shaheed Smriti Journal, 2024)
This study investigates student perceptions of the quality of the Master of Business Studies (MBS) program and the relationship between perceived quality and student satisfaction. A sample of 100 MBS students (25 from each of four campuses) was surveyed in 2023 using a standardized questionnaire. The primary quality metrics were curriculum quality, teacher quality, employability, and credibility. Statistical data analysis techniques were employed to verify the hypothesized relationship between these metrics and student satisfaction. A significant association was found between overall student satisfaction and faculty satisfaction, employability, and credibility. Curriculum quality was not significantly associated with overall student satisfaction. Reputation emerged as the most important factor in determining quality, suggesting that colleges and educational institutions should prioritize this dimension. Curriculum was perceived as the least significant factor, likely due to the lack of variation in curricula across universities. Quality is also correlated with a strong brand name, and a good reputation is likely to be associated with a strong curriculum, faculty, and employability. Educational institutions should also focus on developing strong business relationships that can be accomplished by encouraging and emphasizing graduate employability by indicating the success of their graduates and alumni in their careers and growth.